MEMBANGUN PREDIKSI TERCERAHKAN TENTANG MASA DEPAN DAKWAH LINTAS AGAMA - Zalikha Zalikha (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2015)
Islam considers human being as the most perfect and noble creature from another God's creatures. Perfection and glory are not only from the structure of creation but also from the presence assuming the Caliphate ability. Humans "take care" of the earth is identical to their real work in synergizing the socio-cultural aspects and divine integration, the world and the hereafter, pious and charity, simultaneously and comprehensively. Islamic Dakwah has a responsibility to "greet" all human beings in any position and existence. In line with the principle of inclusiveness, Islam is a religion that really appreciates the differences that exist in the human being as an object of his call. This is why Islam to acknowledge the differences that exists in the human race, ethnicity, skin color, and religion as well as beliefs. Therefore, Islam teaches that wise pattern of dakwah against the basic difference, and condemned the degrading act of mutual confidence others’ status. Mankind is in the creation, which should have the right in the unity of monotheism in Islam. This paper is a bit much to try to open the universality of the human role as the caliph of God on the earth that is manifested in the work and activities of the dakwah of Islam, as well as the vision to be developed is to make Islam belongs to all mankind (rahmatan lil 'alamin) through various recognition on the issue of plurality as a necessity that must be faced and followed up through the Islamic missionary movement wise